Kerajinan Produk Kaum Wanita Amai Setia Kotogadang sebagai Potensi Daerah di Sumatera Barat - Yensharti, Yensharti; Afriwan, Hendra (SPACEPRO: Product Design Jurnal, 2024)
Handicrafts in West Sumatra are an integral part of the arts that have developed over a long time. Koto Gadang, a village in the Agam district, is known as a center of potential crafts. This traditional art marks the cultural identity of Koto Gadang. In the past, the people of Koto Gadang used their crafts, primarily silver and songket, mainly for accessories in wedding ceremonies. The population of Koto Gadang has shifted from agriculture to roles as employees and craftsmen, a change that has been ongoing since the Dutch colonial era. In this context, there is a gender-based division in the choice of professions, where men tend to choose to work in gold and silver crafts, while women opt to become weavers, embroiderers, and lace makers. Significant progress in the advancement of women in Koto Gadang has been greatly influenced by Rohana Khudus. Thanks to her educational initiatives, women began to have the opportunity to go to school and develop skills in sewing, terawang, and lace. The distinctive works of Koto Gadang in this field have been widely known to this day under the umbrella of the Amai Setia association. The crafts of Koto Gadang are the fruit of the hands of the women artisans of the Koto Gadang area, which have high sales value and beauty. It is, of course, incumbent upon us as the community of West Sumatra to preserve and maintain the works of our native village as potential in their respective areas, thus making these areas productive and well-known both regionally, locally, nationally, and internationally."